Sifat Mekanika Kayu Tumeh (Combretocarpus rotundatus Dans) pada Arah Radial - Wahyu Supriyati; Alpian Alpian (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
Communities in Kalimantan areas need wood for building materials. They use Tumeh wood (Combretocarpus rotundatus Dans) because of its found abundantly in forest area in Central Kalimantan. Tumeh is a kind of pioneer. Wood parts affect the quality of wood. The purpose of this study was to study the effect of the radial position on the mechanical properties of wood tumeh. The properties of the wood analyzed is hardness, Modukus of Rupture (MOR) and Mdukus of Elasticity (MOE) (British Standard No.373,1957). Data analysis using Completely Randomized Design (CRD. The results show that the location in the radial direction has no significant effect on hardness, MOR and MOE values.The highest value of hardness and MOR was near the bark and then decreased in the middle and near the heart, respectively. Meanwhile, the highest MOE value is near the heart, then decreases in the middle and near the bark, respectively This research can be continued on the physical and chemical properties of the wood for a more comprehensive understanding. Research in different directions and at different diameters can also be carried out as a comparison.